Irreducible Distal Tibia Physeal Injury with Tibialis Posterior Tendon Interposition. (27th April 2021) - Doshi, Chintan; Dua, Simran; Parikh, Shital N.
Abstract : A 14-year-old basketball player presented with a displaced distal tibia physeal fracture which is typically treated with closed reduction with or without internal fixation. However, repeated attempts at closed reduction failed to align the fracture fragments. At open reduction, tibialis posterior tendon interposition was identified within the fracture site and bowstringing of the tendon prevented closed reduction. A tendon interposition should be suspected when repeated closed reduction attempts fail to achieve satisfactory fracture reduction. The features of tendon interposition should be differentiated from the more common periosteal interposition for physeal fractures of the tibia.